MicroRNAs: emerging biomarkers and therapeutic targets in pancreatic cancer - Yuan, Jiaqian; Yan, Kaiqi; Guo, Yong; Li, Yan (Frontiers in Molecular Biosciences, 2024)
Pancreatic cancer (PC) is a highly malignant disease with high aggressiveness and a dismal prognosis, which is challenging to diagnose clinically early and gains low benefit from standard therapies. MicroRNAs(miRNAs) have become a hot topic in oncology research. Current evidence indicates that miRNAs are regulators involved in the entire process of PC, providing new diagnostic and therapeutic strategies for this fatal disease. Related research has been rapidly updated, making it necessary to review it to propose new directions and ideas and provide guidance for the development of precision medicine for PC. We reviewed the relevant literature through Pubmed, Embase, Web of Science and Medline, showing that abnormally expressed miRNAs in PC patients have the potential to be used as biomarkers for diagnosis and prognosis, highlighting the excellent prospect of combining miRNAs with traditional therapies, and the effective application of these factors for PC, especially miRNA mimics and inhibitors. MiRNAs participate in the entire process of PC and play important roles in diagnosis, treatment and prognosis. They are potential factors in conquering PC in the future.